1991
DOI: 10.1007/bf00025993
|View full text |Cite
|
Sign up to set email alerts
|

Life history adaptations of phyllopods in response to predators, vegetation, and habitat duration in north-eastern Natal

Abstract: Phyllopod populations were monitored in three temporary pools differing in the amount of submerged, peripheral vegetation present, surface area and duration. The effects of these factors on the life history strategies employed by phyllopods were investigated. Triops granarius, various conchostracan species and the anostracan Branchipodopsis sp. inhabited the periphery of two pools where rooted, submerged vegetation was abundant while three Streptocephalus species dominated the central, unvegetated regions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 9 publications
(13 reference statements)
2
20
0
Order By: Relevance
“…All combinations of species of the three orders of large branchiopods were seen recurring over studied area, especially on rocky outcrops. Similar recurring assemblages of different orders have been reported from USA, Mexico and Africa (Hamer and Appleton, 1991b;Thiéry, 1991;Maeda-Martínez et al, 1997). Triops granarius, in the current study was observed only in assemblages, an observation also noted for the congeneric species T. cancriformis (Petrov and Cvetković, 1997;Boven et al, 2008;Waterkeyn et al, 2009).…”
Section: Species Assemblages and Co-occurrencessupporting
confidence: 90%
“…All combinations of species of the three orders of large branchiopods were seen recurring over studied area, especially on rocky outcrops. Similar recurring assemblages of different orders have been reported from USA, Mexico and Africa (Hamer and Appleton, 1991b;Thiéry, 1991;Maeda-Martínez et al, 1997). Triops granarius, in the current study was observed only in assemblages, an observation also noted for the congeneric species T. cancriformis (Petrov and Cvetković, 1997;Boven et al, 2008;Waterkeyn et al, 2009).…”
Section: Species Assemblages and Co-occurrencessupporting
confidence: 90%
“…First, short-lived pools may lack some species because they dry up before species with a long period of development can complete their life cycles, while pools of longer duration provide habitat for both rapidly and slowly developing species (Hamer & Appleton, 1991 ;Hammer & Sawchyn, 1968 ;Retallack & Clifford, 1980;Simovich & Fugate, 1992 ;Thiery, 1991 ;Wiggins et al ., 1980) . Studies of developmental rates under natural temperature and food regimes for the numerous species that are found only in large, deep pools would help to test the hypothesis that these species are unable to inhabit short-lived pools due to developmental time constraints .…”
Section: Discussionmentioning
confidence: 99%
“…Similar cases of temporal separation of species in the same pool are known for other anostracan species (Eng et al ., 1990 ;Simovich & Fugate, 1992 ;Simovich & Hathaway, unpublished data) . Third, large, deep pools may hold more species because they have greater habitat heterogeneity (sensu Williams, 1964) which allows for more niches and greater resource partitioning (Daborn, 1978 ;Hamer & Appleton, 1991 ;Thiery, 1991) . Some evidence for greater habitat heterogeneity in large pools is provided by the zonation of vernal pool plants : in large, deep pools vernal pool plants form concentric rings from the edge to the pool center, each ring being dominated by the species that is best suited for that microhabitat ; in contrast, small, shallow pools are carpeted by only 'edge-adapted' species (Zedler, 1987) .…”
Section: Retallack and Clifford 1980mentioning
confidence: 99%
See 1 more Smart Citation
“…In and regions temporary water communities are characterized by those crustacean orders collectively known as phyllopods (Hutchinson, 1931 ;Rz6ska, 1961 ;Weir, 1969 ;Coetzer, 1981 ;Williams, 1985 ;Seaman & Kok, 1987) . They are the Conchostraca (alternatively classified as two separate orders Spinicaudata and Laevicaudata, Fryer, 1987a) Anostraca and Notostraca, and several species in each order have been found coexisting in the same waterbody (Donald, 1983 ;Brendonck, Thiery & Coomans, 1990 ;Hamer & Appleton, 1991 ;Thidry, 199 1) . They are rare in permanent waters and are frequently referred to as`temporary water taxa' .…”
Section: Introductionmentioning
confidence: 99%